New homocysteine consumption assay for high-throughput screening of human cystathionine-β-synthase - Dalibor Nakládal; Rick Oerlemans; Miroslava Molitorisová; Nikola Chomaničová; Gabriel Zorkócy; Christina Yoseif; Adrianus Cornelis van der Graaf; Stanislav Stuchlík; Guido Krenning; Matthew R. Groves; André Heeres; Zdenko Levarski; et al. (SLAS Discovery)
Hyperhomocysteinemia is a risk factor for cardiovascular disease, neurological disorders, and bone abnormalities. The key enzyme in homocysteine metabolism, cystathionine-β-synthase (CBS) is recognized as a target for new homocysteine-lowering therapies including enzyme replacement and gene therapy. Currently, there are no pharmacotherapies available that enhance CBS activity through its allosteric mechanism. The only known allosteric activator of CBS is S-adenosyl-L-methionine (SAM), which is available as a food supplement, but its effectiveness is limited by low membrane permeability and universal involvement in methylation reactions as a substrate. The discovery of CBS activators in high-throughput screening is challenging due to a lack of dedicated assays. Available HTS-compatible activity assays for CBS rely on measuring the product hydrogen sulfide or methanethiol where the signal increases with increased CBS activity. In the case of fluorescence-based assays, it is challenging to discern activators from autofluorescent compounds.In this study, we introduce a homocysteine consumption assay for isolated human CBS (HconCBS) based on the absorbance of Ellman's reagent. This assay leverages a decrease in signal upon CBS activation, with performance parameters exceeding the requirements for high-throughput screening. In a commercial library of 3010 compounds, the HconCBS assay identified 10 hit compounds as more active than SAM, whereas a fluorescence-based assay using 7-azido-4-methylcoumarin (AzMC) identified 141 hits. HconCBS identified 101 compounds with autoabsorbance which did not include hit compounds, while the fluorescence-based assay identified 383 autofluorescent compounds which included all hit compounds. While 4 out of 10 HconCBS hits were confirmed when purchased from a new source, the compounds affected homocysteine rather than CBS. Nevertheless, HconCBS consistently detected the CBS activator seleno-adenosyl-L-methionine (SeAM) added to 4 library plates and re-discovered the same library hits in 3 out of 4 re-screened plates.Taken together, HconCBS was designed to enable the discovery of allosteric CBS activators with greater reliability than fluorescence-based methods. Despite identifying some compounds that acted on homocysteine rather than CBS, the assay consistently identified the CBS activators SAM and SeAM and demonstrated reproducibility across two screening rounds. These findings establish HconCBS as a valuable tool for identifying potential therapeutic candidates for hyperhomocysteinemia, addressing a key gap in the development of CBS-targeted pharmacotherapies.